Winter habitat use by Black-necked Cranes Grus nigricollis in Tibet - Bishop, Mary A; Zhouma, Canjue; Yanling, Song; Harkness, Jim; Binyuan, Gu (Wildfowl, 1998)
Approximately 66% (3,900) of the world’s Black-necked Crane population winter in south- central Tibet, People’s Republic of China. We collected information on winter habitat use by cranes concurrent with population surveys conducted during four winters: 1990-91 through 1993- 94. Barley and spring wheat stubble was the principal habitat type used by Black-necked Cranes during the day. Secondary river channels and reservoir shorelines were used for roosting. Intensive observations of Black-necked Cranes at two sites found that barley and spring wheat stubble field use exceeded relative availability whereas ploughed fields were underutilized in relation to availability. At both sites the highest percent of cranes feeding and highest use of agricultural fields by cranes occurred during morning hours. Midday hours were characterised by an increased use of riverine habitats for resting. Implementation of Agricultural Management Zones (AMZs) in primary Black-necked Crane wintering areas could serve to minimize conflicts with agricultural interests. We recommend in areas with a high amount of winter wheat, that fewer spring barley and spring wheat fields be ploughed immediately following autumn harvest.